﻿New records for the wild bee fauna (Hymenoptera, Anthophila) of Serbia - Sonja Mudri-Stojnić; Andrijana Andrić; Zsolt Józan; Laura Likov; Tamara Tot; Ana Grković; Ante Vujić (Journal of Hymenoptera Research, 2023)
Numerous scientific projects have been initiated with the aim of tackling the decline in insect pollinators, a crucial group for the functioning of terrestrial ecosystems. One of the first steps is to address information gaps on species spatial distribution, diversity, and abundance that prevent effective conservation actions in Europe. Given that Serbia belongs to the understudied areas, efforts are being made to improve knowledge of its bee diversity and abundance. The present study includes the monitoring of bees at 54 sites, surveyed three times during 2022. The conducted protocol combined two methods, transect walks and pan traps, resulting in the discovery of 312 bee species. The main results present the records of 25 species, not previously mentioned in Serbia, while another important finding is the confirmation of the presence of 26 species, without any available records from the 21st century. Moreover, 79 here examined species were known only from literature-based data. Six of the recorded species are considered threatened and 67 (10 newly recorded) have been assessed as Data Deficient in the European Red List of Bees. Therefore, the present study not only contributes to an update and confirms the list of bee species in Serbia, that now counts 731 species, but also provides additional information about European distribution, required for new assessment at the European level. In addition, the results indicate that the combination of complementary sampling methods is an effective way to assess bee diversity and abundance.